2021
DOI: 10.3390/curroncol28040230
|View full text |Cite
|
Sign up to set email alerts
|

WNT8B as an Independent Prognostic Marker for Nasopharyngeal Carcinoma

Abstract: Background: Members of the Wnt signaling pathway have been shown to play a role in nasopharyngeal carcinoma (NPC) progression. Aim: The purpose of this study was to investigate WNT8B protein expression in NPC patients using tissue microarray (TMA) analysis and to evaluate its correlation with patient survival and clinical parameters. Methods: A total of 82 NPC cases, together with six normal nasopharyngeal tissue samples, were targeted to construct the TMA blocks. The WNT8B protein expression was evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Our transcriptomic analyses resulted in the considerable identification of the Wnt signaling pathway using pathway enrichment analysis. Several Wnt signaling pathway members have previously been identified as being up-regulated in several types of cancers, including NPC ( 19 , 33 35 ). Remarkably, the relapse cases of NPC exhibited the different expression of Wnt signaling compared to the point of diagnosis, including various WNT isoforms, FZD10 , CTNNB1 , and AXIN2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our transcriptomic analyses resulted in the considerable identification of the Wnt signaling pathway using pathway enrichment analysis. Several Wnt signaling pathway members have previously been identified as being up-regulated in several types of cancers, including NPC ( 19 , 33 35 ). Remarkably, the relapse cases of NPC exhibited the different expression of Wnt signaling compared to the point of diagnosis, including various WNT isoforms, FZD10 , CTNNB1 , and AXIN2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, up-regulation of WNT5A has recently been reported in primary NPC tissue samples and cell lines associated with EBV infection ( 36 ), which promotes aggressiveness and stem characteristics in NPC ( 37 ). Our previous tissue microarray analysis illustrated that WNT8B is associated with NPC patients’ survival, which could be used as a prognostic biomarker for NPC patients ( 19 ). As the NPC development comprises multi-step carcinogenesis, the differential expression of Wnt components in our studies may affect the mechanisms of NPC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrant upregulation of Wnt/β-catenin signalling was observed in NPC through the examination of the expression of canonical WNT ligands, such as WNT8B. In the study, a substantial 75.6% of NPC cases were exhibited high expression of WNT8B [ 293 ]. Subsequent observations of NPC patients with overexpressed WNT8B revealed a correlation with shorter survival durations.…”
Section: Molecular Aberrations Exploitation In Npc For Precision Medi...mentioning
confidence: 99%
“…miRNAs are attractive therapeutic targets, either as oncogenes or as repressors. Previous studies have shown that miR-4757-3p is a target miRNA of Wnt5a or Wnt8b in some tumors [ 7 , 8 ]. The marker molecules of the Wnt signaling pathway, Wnt5a, and Wnt8b are required for progression of cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%